2022
DOI: 10.3389/fphar.2022.976561
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus Mongholicus: A review of its anti-fibrosis properties

Abstract: Background: Fibrosis-related diseases (FRD) include cerebral fibrosis, pulmonary fibrosis, cardiac fibrosis, liver fibrosis, renal fibrosis, peritoneal fibrosis, etc. The effects of fibrosis can be severe, resulting in organ dysfunction, functional decline, and even organ failure, which can cause serious health problems.Aim: Currently, there is no effective modern medicine for anti-fibrosis in the clinics; however, Chinese medicine has a certain beneficial effect on treating such diseases. Astragalus Mongholic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 144 publications
0
7
0
Order By: Relevance
“…As effective bioactive components of A. membranaceus and L. chuanxiong , these factors have similar positive pharmacological activities, including anti-inflammatory, antioxidant, and immunoregulatory effects [ 44 46 ]. Existing evidence has demonstrated that AS-IV exerts antifibrotic effects through multiple signaling pathways in various fibrotic diseases, including TGF-β1/SMAD, p38 MAPK, NLRP3 inflammasomes, NOX4/p38 MAPK, and others [ 16 18 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…As effective bioactive components of A. membranaceus and L. chuanxiong , these factors have similar positive pharmacological activities, including anti-inflammatory, antioxidant, and immunoregulatory effects [ 44 46 ]. Existing evidence has demonstrated that AS-IV exerts antifibrotic effects through multiple signaling pathways in various fibrotic diseases, including TGF-β1/SMAD, p38 MAPK, NLRP3 inflammasomes, NOX4/p38 MAPK, and others [ 16 18 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has played a very large role in the prevention and treatment of CKD [ 56 , 57 ]. Recently, accumulating articles have reported that Astragalus Mongholicus (AM) , as a traditional Chinese herbal medicine, has a rich medicinal value, and recently, its anti-fibrosis effect has been increasingly investigated [ 58 ]. AS-IV, the main active component of saponins extracted from AM, has been reported to have various pharmacological activities, including regulation of the calcium ion equilibrium [ 59 ] and anti-oxidative [ 60 ], anti-apoptotic [ 61 ], and anti-fibrosis [ 62 ] functions.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no specific treatment for IPF, but traditional Chinese medicine (TCM) has distinct superiorities in IPF therapy, and numerous studies have revealed that TCM can mitigate the symptoms and lung function of IPF patients [5]. Astragalus is one of the most frequently used supplements in the treatment of pulmonary fibrosis [6]. Its main active ingredients include saponins, flavonoids, polysaccharides, alkaloids and so on [7].…”
Section: Introductionmentioning
confidence: 99%